Penerapan Pasal 340 KUHP Mengenai Tindak Pidana Pembunuhan Berencana: Analisis Putusan Nomor 1474Pid.B2019PN Dps: Bima Guntara, Ayni Suwarni Herry*, Dian Mohamad Eron Siata - Bima Guntara; Ayni Suwarni Herry; Dian Mohamad Eron Siata (Samudra Publisher, 2024)
This research was conducted to find out and examine the application of Article 340 by the judge in handing down a criminal decision for the defendant in the crime of murder of Halimah in Decision Number 1474/Pid.B/2019/PN Dps. As well as to find out and analyze whether the elements contained in Article 340 of the Criminal Code have been fulfilled or not so that the defendant Rudianto was sentenced to 16 years in prison. This research uses normative juridical research methods, namely those carried out based on main legal materials by examining theories, concepts, legal principles, and statutory regulations related to this research. Based on the analysis of the facts and data that the author has obtained, the author finally concludes: 1. That the judge in applying article 304 in Decision Number 1474/Pid.B/2019/PN Dps) did not properly consider whether or not the planned elements had been fulfilled in advance. 2. That the element was planned in advance, namely, in a calm atmosphere to decide the will. From the emergence of the will to the implementation of the will, there was sufficient time available, and the implementation of the will (action) in a calm atmosphere did not result in the murder of Halimah.